Pengembangan Nilai-nilai Cinta Laut bagi Anak Suku Laut di Pulau Lipan, Kabupaten Lingga - Susanna Nurdjaman; Ivonne Milichristi Radjawane; Jeremy Nugraha Pongrekun; Affan Fadli Rahmadian; Muhammad Ikhwan Fadilah Giantara; Erica Maharani Budiono (Institut Pertanian Bogor, 2024)
The empowerment of marginalized communities has increasingly become a crucial issue and program in Indonesia today. The central and local governments strive to empower these communities, including the Sea Tribes on Pulau Lipan. In practice, marginalized community groups are increasingly ignored by the government, as experienced by the Sea Tribe on Lipan Island. This community service program seeks to implement development in the education sector regarding the values of love for the sea for Sea Tribe children at State Elementary School (SDN) 006 Selayar. The curriculum used is prepared by considering the condition analysis made by the service team. This activity aims to foster love and awareness of marine ecosystems in Sea Tribe children so that they can maintain marine conservation and ensure wiser use of the ocean. The method used is to teach children about the sea through exciting and fun interactions about the love of the sea and games. Apart from that, the service team also established a mini library for the Sea Tribe community. The results of the implementation of activities show that the curriculum and method of delivering material and developing skills are appropriate for Sea Tribe students in receiving marine education, which can be measured from the level of children's interest and the relevance of the material that can be applied. Two-way, applicable education effectively educates sea tribe children about maritime affairs. Several obstacles are also faced in implementing the following program, where it is necessary to design a curriculum design that can provide learning to students in a sustainable, structured, practical, and memorable manner so that the instillation of maritime values can be enhanced and not just incidental as happens in the program.